2010
DOI: 10.1007/s00167-010-1235-9
|View full text |Cite
|
Sign up to set email alerts
|

Graft length change and radiographic assessment of femoral drill hole position for medial patellofemoral ligament reconstruction

Abstract: The femoral tunnel position is reaffirmed to be an essential determinant for the graft length change in the MPFL reconstruction. Both graft length change measurements and intraoperative radiographic assessment are practical for proper graft placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 28 publications
3
41
1
Order By: Relevance
“…2,23,26,29,34,35,37 According to our results, 2 virtual ligaments including the medial femoral epicondyle (C1, C2) were less isometric than the other 6 ligaments (Figure 4); that is, the medial femoral epicondyle represents a less isometric point than the other 3 femoral points. This finding shows that, similar to previous in vitro studies, length changes of the reconstructed MPFL depend principally on the femoral attachment site.…”
Section: Discussionmentioning
confidence: 71%
“…2,23,26,29,34,35,37 According to our results, 2 virtual ligaments including the medial femoral epicondyle (C1, C2) were less isometric than the other 6 ligaments (Figure 4); that is, the medial femoral epicondyle represents a less isometric point than the other 3 femoral points. This finding shows that, similar to previous in vitro studies, length changes of the reconstructed MPFL depend principally on the femoral attachment site.…”
Section: Discussionmentioning
confidence: 71%
“…8 In addition, the femoral attachment position is reportedly critical to graft length changes in MPFL reconstruction, and the femoral tunnel center determines the graft length change pattern. 47 The same authors reported that length change pattern also determined early knee range of motion recovery and postoperative patellar alignment and suggested femoral tunnel position as being important to achieve good postoperative outcome. Furthermore, the most important factor affecting graft isometry is reported to be the position of the femoral attachment site.…”
Section: Discussionmentioning
confidence: 96%
“…First, the femoral anchoring site of the reconstructed MPFL is deviated slightly posteriorly, although still within the range of the reported area for the anchoring site, [13][14][15][16][17][18] to meet the demand of patients to sit squarely after surgery. When this point is used, the distance between the patellar and femoral attachment sites gradually shortens as the knee joint bends to more than 60 of flexion, regardless of the site of patellar attachment.…”
Section: Discussionmentioning
confidence: 83%